THE IMPLEMENTATION OF INFORMATION GAP ACTIVITY AND JUMBLED SENTENCE GAME IN TEACHING READING COMPREHENSION - Galfry Patty; Rizqi Claudia Wardani; Nurteteng (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The implementation of Information Gap Activity and Jumbled Sentences Game in Teaching Reading Comprehension at Eight Grade Smp Muhammadiyah 2 Mariyai Sorong Regency Thesis English Education Department faculty of language sosicial and sport education university of pendidikan muhammadiyah sorong,Mey 2023. The objective of this research is to know whether the implementation of information gap Activity and jumble sentence game has impact or not on students’ reading at smp muhammadiyah 2 mariyai sorong regency. The research used pre-experimental quantitative research design with design is one group pretest-posttest. The population of this research was the eight grade students’ at Smp Muhammadiyah 2 Mariyai Sorong Regency. The researcher choose this class because there are some problems on students’ reading. In thecollecting data researcher used multyple choice with 20 questions for the pretest and posttest. To analyzed the data the researcher use SPSS 20 version. The result finding of the research showed that the result of pair sample T test(0,00) the categorized was impact .In addition to result of the pair sample T-test is P value (0.00)<(0,05).it means that HO was rejected and Ha was accept. The alternative hypothesis (Ha) was there is an impact in teaching reading using information gap and jumbled sentence game